Automatic localization of the prostatic urethra for image guided radiation therapy. (September 2021) - Nasser, Nicola J.; Klein, Jonathan; Fenig, Eyal; Agbarya, Abed
Highlights: Prostatic urethra can be used for image guided radiation for prostate cancer. Computer "finds" the urethra by digital subtraction of scans with / without contrast. Urethra segmentation used to setup the patient and position prostate as in simulation. A catheter with continuous aerated gel flow is used to detect the urethra under US. Abstract: Treatment of prostate cancer with radiation therapy (RT) requires image guided RT (IGRT) to focus the radiation on the target volumes while minimizing doses to organs at risk. Here we describe a urinary catheter that allows imaging of the prostatic urethra and uses it for automatic localization of the prostate for IGRT. The catheter has a contrast lumen that can be empty or full with contrast. Computerized tomography is performed twice, with contrast lumen empty and full, allowing urethral autosegmentation using digital subtraction. Under ultrasound, continuous urethral visualization is possible by pumping aerated gel in- and out of the contrast lumen.